Recurrent cyanotic episodes with severe arterial hypoxaemia and intrapulmonary shunting: a mechanism for sudden death. Issue 9 (September 1990) - Southall, D P; Samuels, M P; Talbert, D G
Abstract : The pathophysiology of recurrent cyanotic episodes has been investigated in 51 infants and children. Episodes began at a median age of 7 weeks (range 1 day to 22 months, 39 at less than 4 months). They were characterised by the rapidity of onset and progression of severe hypoxaemia with early loss of consciousness from cerebral hypoxia. The most common precipitating factor was a sudden naturally occurring stimulus from pain, fear, or anger. In uncontrolled trials, cyanotic episodes were reduced in frequency and severity by tetrabenazine (n = 15) and additional inspired oxygen (n = 10). Eight patients died suddenly and unexpectedly (four during cyanotic episodes). Twenty eight patients underwent physiological studies during cyanotic episodes. There was no evidence of seizure activity at the onset and although prolonged absence of inspiratory effort with continued expiratory efforts was common, breathing sometimes continued. Episodes were not caused by upper airway obstruction and sometimes occurred during positive airway pressure ventilation. The rapidity of fall in arterial oxygen pressure and continued breathing suggested a right to left shunt of sudden onset. The results of contrast echocardiography and lung imaging studies confirmed that this was occurring within the lungs. These cyanotic episodes included both intrapulmonary shunting and prolonged expiratory apnoea. They are best explained by interactions between central sympathetic activity, brainstem control of respiration and vasomotor activity, reflexes arising from around and within the respiratory tract, and the matching of ventilation to perfusion in the lungs. They are a cause of sudden unexpected death in infancy and early childhood.